Primary Biliary Cirrhosis in a Male: A Case Report and Review of Literature - Afroze, Samira Rahat; Rahim, Muhammad Abdur; Hasan, Md Mehedi; Afroz, Farzana; Haque, Hasna Fahmima; Ahmed, Jamal Uddin; Ahmed, AKM Shaheen; Hossain, Md Delwar; Rahman, Md Raziur; Musa, AKM; Uddin, Khwaja Nazim (Journal of Medicine, 2015)
A middle aged woman presenting with fatigue, pruritus, xanthelesma and hepatomegaly remains the typical presentation of primary biliary cirrhosis. Here, we present a case of primary biliary cirrhosis occurring in a male patient, who presented with fatigue and pruritus, had hepato-splenomegaly, raised serum alkaline phosphatase, positive anti-mitrochondrial antibody and negative antinuclear antibody. J MEDICINE July 2015; 16 (2) : 128-131